Redescription of two troglobiotic species of the genus Pseudosinella Schäffer, 1897 (Collembola, Entomobryidae) from the Western Carpathians - Kováč, Ľubomír; Rusek, Josef (Zootaxa, 2012)
Two troglobiotic species of the genus Pseudosinella Schäffer, 1897 from the Western Carpathians are redescribed, P. ag-gtelekiensis (Stach, 1929) and P. paclti Rusek, 1961. P. aggtelekiensis has endemic distribution restricted to the Slovak-Aggtelek Karst region in Slovakia and Hungary. It shows higher level of troglomorphy (elongation of antennae, basal dis-placement of ungual teeth concurrent with their reduction) probably representing a descendant of the older phyletic Lep-idocyrtus-Pseudosinella lineage. P. paclti, distributed in caves of several karstic regions in central Slovakia, is characteristic with medium level of troglomorphy.